Evaluation of self-healing capability of a polycaprolactone interphase in epoxy/glass composites. (June 2023) - Simonini, L.; Mahmood, H.; Dorigato, A.; Pegoretti, A.
Abstract: Self-healing composites possess the ability to self-repair in response to damage, either autonomously (i.e., without human intervention), or when subjected to an external stimulus such as heat. This work was focused on the evaluation of the interfacial self-healing capability of glass fiber-reinforced epoxy composites in which polycaprolactone nanoparticles were deposited as a coating on the surface of the fibers. Polycaprolactone nanoparticles were synthesized following solvent displacement technique and deposited on the fibers (with and without the sizing agent) by electrophoretic deposition. Scanning electron microscopy revealed high-quality nanoparticles deposition, with good level of homogeneity and compactness. Epoxy microdroplets were cured on the fibers and microdebonding tests were performed to estimate the interfacial self-healing capability, calculated as the ratio of the interfacial shear stress measured before and after the thermal mending process. An interfacial adhesion recovery of about 50 % was obtained, thus indicating an interfacial self-healing capability induced by the polycaprolactone nanoparticles.